Dose-response aggregometry--contribution to the precise platelet function evaluation - Jancinová, V; Nosál, R; Petríková, M (Thrombosis research, 1992)
A method for the determination of blood platelet aggregability as the function of ADP concentration is described. Individual platelet aggregability was characterised by means of parameters of the sigmoidal relationship between the dose of the aggregating reagent and the aggregation curve amplitude. The method was applied to establish ADP-induced aggregability of various mammalian species. The aggregation curves of rabbit and rat platelets reached significantly lower maximum amplitudes than those of human and dog platelets. The eman concentration of ADP was significantly higher in dog platelets and the slope of the dose-response curve was significantly steeper in rat platelets compared to the other species studied. Some of the causes of individual intra-species ADP-induced aggregation variability revealed by means of dose-response aggregometry are discussed.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; Reproducibility of Results; Rats; Platelet Function Tests; psi; reprodukovatelnost výsledků; Dogs; mužské pohlaví; vyšetření funkce trombocytů; krysa rodu Rattus; ženské pohlaví; zvířata; Humans; králíci; Rabbits; Species Specificity; agregace trombocytů; druhová specificita; Platelet Aggregation; Female; lidé; Male; Animals